PENGARUH ECONOMIC FREEDOM DAN PENDAPATAN PER KAPITA TERHADAP INDEKS PEMBANGUNAN MANUSIA - Agustina Suparyati (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2014)
This study aims to determine the effect of economic freedom and national income per capita of the human development index. Countries will be classified into 4 groups according to the classification in the HDI are very high human development (with an HDI of 0788 or above), high human development (with an HDI of 0677 to 0.784), medium human development (HDI of 0488-0669), and low human development (HDI of less than 0488). The analysis method used in this study is a model of data panel to investigate the influence of Economic Freedom and Income per capita of the HDI. The results showed that for the group of countries very high human local development per capita income is only significant effect on the HDI, for the group of countries High human development and medium human development only economic freedom that affects the HDI, while the low human development group showed that income per capita and Economic Freedom does not affect the HDI.